2021
DOI: 10.48550/arxiv.2109.14018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A robust and efficient line search for self-consistent field iterations

Michael F. Herbst,
Antoine Levitt

Abstract: We propose a novel adaptive damping algorithm for the self-consistent field (SCF) iterations of Kohn-Sham density-functional theory, using a backtracking line search to automatically adjust the damping in each SCF step. This line search is based on a theoretically sound, accurate and inexpensive model for the energy as a function of the damping parameter. In contrast to usual SCF schemes, the resulting algorithm is fully automatic and does not require the user to select a damping. We successfully apply it to a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…DFTK.jl has already been used to investigate new developments in the self-consistent field procedure. 63,64 The success of DFTK.jl has shown that Julia is not only viable, but effective at tackling chemical problems and producing high-performance software.…”
Section: The Julia Programming Languagementioning
confidence: 99%
“…DFTK.jl has already been used to investigate new developments in the self-consistent field procedure. 63,64 The success of DFTK.jl has shown that Julia is not only viable, but effective at tackling chemical problems and producing high-performance software.…”
Section: The Julia Programming Languagementioning
confidence: 99%